The interface between competition and intellectual property law : finding common ground and resolving the tensions between these areas of law from a South African perspective - Dercksen, Juletha-Marie (Stellenbosch : Stellenbosch University, 2023)
Thesis (LLD)--Stellenbosch University, 2023.